Boardroom gender diversity and intellectual capital efficiency: evidence from China. Issue 4 (6th November 2017) - Nadeem, Muhammad; De Silva, Tracy-Anne; Gan, Christopher; Zaman, Rashid
Abstract : Purpose: This paper aims to investigate the relationship between boardroom gender diversity and intellectual capital (IC) efficiency in China – while the previous literature focuses only on traditional accounting-based performance measures such as return on assets or Tobin's Q. Design/methodology/approach: A well-developed Arrelano–Bond generalised method of moment (GMM) is applied to account for endogeneity – mainly because of simultaneity and unobserved heterogeneity. Moreover, this study uses an adjusted-value added intellectual coefficient (VAIC) model to measure the IC efficiency of 906 Chinese listed firms for 2010-2014. Findings: The empirical analysis shows a significant relationship between gender diversity and IC efficiency, in static ordinary least square estimation, but this disappears when endogeneity is accounted for using dynamic GMM. This insignificant relationship remains consistent, even when two alternative proxies of gender diversity, i.e. the Blau index and the women dummy, are used. Practical implications: This study provides some useful insights into the traditional Chinese corporate structure where females cannot use their powers to bring corporate changes in firms. The findings show that gender-related stereotypical attitudes continue to exist in China. The regulators, therefore, should look into strengthening gender related regulations – which are currently non-existent in China. Originality/value: This is the first study of its kind to investigate the relationship between gender diversity and IC efficiency in China using the A-VAIC model and GMM to mitigate endogeneity.